PENINGKATAN HASIL BELAJAR IPA DENGAN STRATEGI PEMBELAJARAN KOOPERATIF GROUP INVESTIGATION DI KELAS IX-1 SMP NEGERI 2 KUTALIMBARU TAHUN AJARAN 2018/2019 - Lasmarita Tanjung (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2020)
The use of the group investigation cooperative learning strategy could improve the science learning outcomes of students IX-1 SMP Negeri 2 Kutalimbaru in the 2018/2019 academic year. This research is a class action research with 2 cycles, each cycle consisting of 4 activities, namely planning, action, observation, and reflection followed by planning in the next cycle by utilizing the results of previous reflections. teaching science on the subject of food production to 32 students of IX-1 SMP Negeri 2 Kutalimbaru for the 2018/2019 academic year. The findings of the study showed that science learning with the implementation of the cooperative learning strategy group investigation could improve student learning outcomes as evidenced by the increase in learning outcomes in each cycle, from an average of 65.31 to an average of 81.41.